Dinamika Pembangunan Manusia Inklusif dan Berkelanjutan di Wilayah Kepulauan: Studi Kasus Kota Baubau, 2005-2023 - Saksono, Herie; Utami, Karina Juniarti (Kainawa: Jurnal Pembangunan dan Budaya, 2024)
This study examines the dynamics of human development in Baubau City, an archipelagic region in Eastern Indonesia, over two decades (2005–2023). This period was selected to reflect governance transformation following the enactment of Law No. 32 of 2004 on Regional Governance, aimed at strengthening regional autonomy. The research focuses on exploring how the archipelagic characteristics influence the trajectory of human development and identifying challenges and opportunities within the geographical context, as highlighted through the progression of the Human Development Index (HDI). Using a qualitative case study approach, data were analyzed through the interactive model of Miles, Huberman, and Saldaña, taking into account the socio-economic complexities of archipelagic regions. The study reveals that Baubau City's HDI increased from 69.70 (2005) to 79.00 (2023), with an average annual growth of 0.70%. The health dimension experienced significant improvement, marked by an increase in Life Expectancy (LE) from 69.00 years to 74.53 years. The education dimension also demonstrated growth, as the Mean Years of Schooling (MYS) increased from 8.80 to 11.02 years, reflecting strengthened human capital. In the economic dimension, Per Capita Income rose substantially from IDR 591,900 to IDR 11,207,000, though this growth was not consistently accompanied by equitable distribution, underscoring the need for inclusive policies. The novelty of this research lies in its integration of regional development perspectives and archipelagic characteristics in analyzing the dynamics of human, economic, and social development within an archipelagic context. The study recommends strengthening locality-based interventions that consider the geographical uniqueness of archipelagic regions, focusing on education, health, and economic equity to accelerate human development and achieve sustainable development goals.